Efficacy of antimicrobial therapy and topical disinfectants in the purulent surgery department of a multidisciplinary hospital - O.V. Mironenko; A.A. Tovanova; A.A. Panteleev; M.I. Podboronov (Disinfection affairs, 2026)
Presentation at the scientific-practical conference with international participation «Perspectives of disinfectology. Disinfection measures in emergency situations and in the territories of natural foci of infectious diseases» (September 22-23, 2026, Moscow)